Human Papilloma Virus self-sampling performance in low- and middle-income countries - Kamath Mulki, Ashwini (BMC Womens Health, 2021)
BACKGROUND: Screening for HPV has led to significant reductions in cervical cancer deaths in high-income countries. However, the same results have not been achieved in low- and middle-income countries (LMICs). HPV self-sampling is a novel approach that could improve screening rates. METHODS: This study’s objective is to summarize the recent literature on HPV self-sampling in LMICs, focusing on sensitivity/specificity, and feasibility/acceptability of self-sampling compared to traditional screening methods. We conducted a PubMed search for articles published in English within the last 10 years on self-sampling in LMICs. RESULTS: Fifty eligible articles from 26 countries were included, 19 of which came from sub-Saharan Africa and 18 from Latin America/Caribbean. Seven studies examined sensitivity, with five reporting rates higher than 91%. Six reported on specificity, which was also very high at 86–97.8%. Six studies examined self-sampling concordance with provider-collected sampling, with concordance rates ranging from 87 to 97.5%. A total of 38 studies examined the feasibility/acceptability of HPV self-sampling. Participation rates were very high in all studies, even when self-sampling was done at participants’ homes (over 89% participation). Overall, participants reported that HPV self-sampling was easy to perform (75–97%, 18 studies), painless (60–90%, nine studies), and preferred over provider-collected sampling (57–100%, 14 studies). Eight studies reported follow-up rates for participants who completed self-sampling; however, these rates varied widely-from 13.7 to 90%. The major benefits of self-sampling include convenience of screening from home, less embarrassment, and less travel. Improved education and awareness of self-sampling, combined with support from community health workers, could reduce perceptions of self-sampling being inferior to provider-collected sampling. Improving follow-up of abnormal results and improving linkages to treatment are also essential. CONCLUSION: Our literature review highlights HPV self-sampling is a well-performing test that shows promise in terms of expanding screening efforts for the prevention of cervical cancer-related deaths in LMICs.